An Analysis of Quality Criteria to Determine the Improvement Priority Attributes - Sihombing, Haeryip; Yuhazri, Yaakob; YAHAYA, SAIFUDIN HAFIZ; Sivarao, Subramonian; Hazwan, M.A (Universiti Teknikal Malaysia Melaka, 2012)
This study is focused is on how to find out the improvement priorities for customer satisfaction. In this study, the Voice of Customer (VoC) is identified, analyzed, and evaluated through the service attributes of SERVQUAL. Kano Method and Likert Scale were used in the questionnaire developed in order to explore customer satisfaction, while the intagration of ranking level, customer satisfaction-dissatisfaction (CD-DS) values and graph, and their correlation are used to find out what the attributes of service delivered as the elements for improvement required. To find the correlation and the relationship among the service elements, calculation using SPSS were constructed into comparison between Kano, Functional, and Dysfunctional table where "the electronic service to communicate (KI) with" of the service attributes of Responsiveness is as the first priorities improvement required by customer.